Reconstruction Of â€œObstruction Of Justiceâ€ As A Criminal Act In The Law On Eradicating Corruption In Indonesia - Samsul HUDA; Bambang SUGIRI; Nurini APRILIANDA; Heru R. HADI (International Journal of Environmental, Sustainability, and Social Science, 2022)
Corruption is a special criminal act, qualified as an ordinary crime but must be eradicated in extraordinary ways. In Indonesia, it is not only an extraordinary method but also an institution with extraordinary authority formed because corruption has become a systemic and systematic disease of society. Criminalizing the act of "obstructing the judicial process" is one way to eradicate corruption extraordinarily. The positive law has already regulated it, but it needs to be strengthened by ratifying UNCAC 2003 so that the norms governing the offense can be universally recognized. This study aims to synchronize and harmonize the norms that have been regulated in positive law with the new norms regulated in UNCAC 2003 to avoid misperceptions in its implementation. The normative method is used by examining philosophically and juridically through principles and theories that develop and are associated with emerging empirical problems. Several legal cases are used to analyze the philosophical and juridical problems and to find weaknesses in the "obstruction of justice" offense norm. It needs to be reconstructed to ensure legal certainty and justice better. In the end, the goal of eradicating corruption can be achieved, without violating the proper criminal procedural law and placing interested parties, both from the perspective of the perpetrators and victims.